Analisa Dan Perancangan Keamanan Jaringan End User Dari Serangan Exploit Menggunakan Metode Penetration - Ari Prayoga Hutabarat; Haeruddin haeruddin (Program Sarjana Sistem Informasi, Universitas Internasional Batam, 2020)
As global information and communication technology develops, everyone must be able to accept these changes. At this time everyone must compete in learning the development of technology, if they cannot keep up with the development of the technology, they will not be able to survive technological developments and miss technology. With the development of technology, increasing use of technology will increase. So that many people will learn the latest technology. With so many people who are just learning about technological developments, there are many cases of cybercrime that use people who are not